Effect of an experimental silica-nylon reinforcement on the fracture load and flexural strength of bisacrylic interim partial fixed dental prostheses - Almeida, Carolina Souza [UNESP]; Amaral, Marina; De Cássia Papaiz Gonçalves, Fernanda [UNESP]; De Arruda Paes, Tarcisio José [UNESP] (Elsevier, 2016)
Statement of the problem. Materials used in the fabrication of interim restorations usually have mechanical properties inferior to those used in definitive prostheses. Various techniques may be used to reinforce these materials. Purpose. The purpose of this in vitro study was to evaluate the fracture strength of interim partial fixed dental prostheses (FDPs) with and without an experimental silica-nylon reinforcement placed in different orientations (horizontal or vertical) before and after thermocycling and to evaluate the flexural strength of the bisacrylic resin used for fabricating these prostheses. Material and methods. For fracture strength testing, 72 four-unit interim partial FDPs were fabricated from bisacrylic resin and divided into 3 groups: no reinforcement, horizontal reinforcement, and vertical reinforcement. Half of the specimens from each group were thermocycled before testing (1000 cycles between 5°C and 55°C) (n=12). An increasing load was applied to the center of the prosthesis until fracture. The flexural strength of bisacrylic resin reinforced with the experimental mesh was measured by using a 3-point bending test with 25×10.5×3.3 mm bars of resin, with or without thermocycling. The results were evaluated with analysis of variance and Kaplan-Meier survival analysis (α=.05). Results. The results showed that incorporating the experimental silica-nylon reinforcement in a horizontal orientation provided the highest values of fracture strength for the 4-unit partial FDPs. Reinforcement also enhanced the flexural strength values of bisacrylic resin bars. Conclusion. Silica-nylon reinforcement is an effective method of increasing the strength of interim restorations.